IMPACT OF PERTAMINA CSR ON COMMUNITY INTEREST FOR TURTLE CONSERVATION ON THE ISLAND OF SERANGAN - G., SUARTA; DANANJAYA, I G. A. N.; MELATI, N. P. Y. (Majalah Ilmiah Peternakan; Vol 25 No 3 (2022): Vol. 25 No. 3 (2022), 2022)
In order to conserve turtles carried out by the community through the Turtle Conservation and Education Center (TCEC), PT Pertamina (Persero) DPPU Ngurah Rai through the Corporate Social Responsibility Program strongly supports the conservation and conservation of turtles on Serangan Island. The purpose of this study was to analyze the social and CSR impact of Pertamina on public interest in preserving the turtle economy on Serangan Island. This research was conducted on Serangan Island and the selection of this location was determined purposively. The population in this study found 137 people while the sampling technique in this study used a simple random sampling method of 42 people. Data analysis in this research is descriptive qualitative and quantitative. The resul- ts showed that the social impact of Pertamina’s CSR on public interest in turtle conservation on Serangan Island was seen from community development, community participation, and preservation of conservation programs in the good category with a score of 3.96. Meanwhile, the economic impact of Pertamina’s CSR on public interest in turtle conservation on Serangan Island which consists of indicators of employment, increased income, and tourism potential is in the good category with a score of 4.02. Suggestions for the community are expected to continue to monitor the conservation and preservation of turtles in order to increase tourism potential on Serangan Island.